A Unique Structural Highly Compacted Binder‐Free Silicon‐Based Anode with High Electronic Conductivity for High‐Performance Lithium‐Ion Batteries. Issue 2 (16th November 2021) - Dong, Zhe; Du, Wubin; Gu, Haitao; Long, Yingying; Zhang, Chenyang; Chen, Gairong; Feng, Zhenhe; Sun, Wenping; Jiang, Yinzhu; Liu, Yongfeng; Yang, Yaxiong; Gan, Jiantuo; et al.
Abstract : Herein, a unique structural Si‐based anode with high electronic conductivity, high compact density, and with no traditional organic binder is put forward. By adding a few amounts of Sn to the Si anode material, followed by carbonization of the organic binder after the general anode preparation and subsequently hot pressing, Sn melts and squeezes during hot pressing, bonding strongly the Si particles, and an interlayer of Cu3 Si/Cu3 Sn is in situ formed at the interface of the Si‐based active materials and the Cu current collector, resulting in a metallurgical bonding between them. The organic binder‐derived carbon coats on the Si particles, coupling with the squeezed Sn and the Cu3 Si/Cu3 Sn interlayer, and a highly electron conductive skeleton is formed. The skeleton also offers a highly stable structural integrity of the electrode during cycling. With an optimization of the hot‐pressing pressure, the Si‐based anode shows superior cycling stability and rate performance. As the active materials are almost compacted to half of its initial thickness, the electrode has potential for high volumetric capacity. The fabrication method is new for Si‐based anodes of high compact density. The work provides new insights into the development of advanced silicon‐based anodes for lithium‐ion batteries. Abstract : A novel Sn‐bonded Si anode coated with PVDF‐derived carbon is proposed. During hot pressing, Cu3 Si as well as Cu3 Sn is in situ formed at the interface of the active materials and the Cu current collector. In addition, Sn melts and serves as the metallic binder during hot pressing, which also results in a strong metallurgical bonding between electrode materials.